2015
DOI: 10.1002/app.42252
|View full text |Cite
|
Sign up to set email alerts
|

Graphene‐modified poly(lactic acid) for packaging: Material formulation, processing and performance

Abstract: Manufacturing of plastics by compostable polymers is of crucial relevance to limit the environmental impact and reduce oil consumption. Performance of compostable polymers is often mediocre, although they could be improved by physical and chemical routes. In this work, Poly(Lactic Acid) (PLA) is modified for improved performance by two different routes: (1) by physically dispersing Graphene Nano-Platelets (GNP) in the organic matrix; (2) by the physical dispersion and covalent bonding of PLA and Amino-Function… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
12
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 21 publications
(12 citation statements)
references
References 27 publications
0
12
0
Order By: Relevance
“…However, the light transmittance for the composite film was significantly decreased to only ca 20% at 600 nm, while the pure thiol‐ene film exhibited high transparency with a transmittance value of 88%. Other researchers also found that the addition of graphene nano‐platelets or nanoparticles could increase the pencil hardness of the materials …”
Section: Resultsmentioning
confidence: 94%
“…However, the light transmittance for the composite film was significantly decreased to only ca 20% at 600 nm, while the pure thiol‐ene film exhibited high transparency with a transmittance value of 88%. Other researchers also found that the addition of graphene nano‐platelets or nanoparticles could increase the pencil hardness of the materials …”
Section: Resultsmentioning
confidence: 94%
“…18 Several authors have reported barrier improvements by using graphene sheets or graphene oxide in polymer composites. [57][58][59][60] The mechanisms underlying the barrier improvement of nanoplate-based composites is the wellknown 'tortuous path' principle, schematized in Figure 2.…”
Section: Nanomaterial-polymer Composites For Improved Barrier Propertiesmentioning
confidence: 99%
“…The research group is using a combination of graphene-enhanced and carbon nanotube-enhanced 3D printing materials to tailor the properties. Research is also focusing on modifying polymers with graphene [36]. Although graphene has also been referred to as a remarkable material, homogeneous mixtures of graphene and polymers are essential to exploit the unique proper-ties [37].…”
Section: Polymer Integrationmentioning
confidence: 99%